2021
DOI: 10.4236/ijohns.2021.103014
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method of Managing the Alveolar Antral Artery during Sinus Lift Surgery

Abstract: The alveolar antral artery resides lateral to the maxillary sinus and can lead to complications in sinus lift surgery. Traditional approaches that decrease intraoperative bleeding into the surgical field include vessel preservation using multiple bony windows or neutralizing the vessel at the surgical site. Unfortunately, these methods are technique sensitive, time intensive, and may lead to hemosinus and graft loss. The variable distance from the crest of the alveolar ridge and vessel diameter further complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
7
1
1
Order By: Relevance
“…Our study calculated a 69% prevalence rate in finding the AAA on CT images, which is slightly higher compared with previous CT studies with prevalence rates that ranged from 47% to 64.5% 7,8 . Our lower detection rate compared with those of cadaveric studies may be related to the extrabony vessel occurring lateral to the sinus wall; the diameter of the AAA being too small (0.9–1.5 mm); or the intrasinus vessel occurring within the sinus, between the sinus wall and membrane 9,10 . However, in studies using cone-beam CT (CBCT), the prevalence is higher (52.8%–94.4%) because CBCT has better resolution, such as a larger voxel size 5 .…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Our study calculated a 69% prevalence rate in finding the AAA on CT images, which is slightly higher compared with previous CT studies with prevalence rates that ranged from 47% to 64.5% 7,8 . Our lower detection rate compared with those of cadaveric studies may be related to the extrabony vessel occurring lateral to the sinus wall; the diameter of the AAA being too small (0.9–1.5 mm); or the intrasinus vessel occurring within the sinus, between the sinus wall and membrane 9,10 . However, in studies using cone-beam CT (CBCT), the prevalence is higher (52.8%–94.4%) because CBCT has better resolution, such as a larger voxel size 5 .…”
Section: Discussioncontrasting
confidence: 56%
“…On the contrary, several previous studies 12–14 have documented higher prevalence rates of intrasinus AAAs than intraosseous AAAs. Not only a septated sinus, the bifid vessel of the AAA may also complicate the surgery and increase the risk of hemorrhage 10 . The investigation has revealed that the presence of 2 anastomotic connections (intraosseous and extraosseous) constructing a bifurcated arterial arcade, which supplies the lateral wall of the antrum as well as specific segments of the alveolar process 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In case of severe bleeding from artery in diameter larger than 3 mm, the preventive ligature can be considered or flap elevation with preparation to ligature of distal aspect, can be considered ( Yang & Lee, 2021 ). Figures 14 and 15 show the result of an alternative surgical approach—an internal sinus lift which is also a very conservative treatment option, albeit with some limitations—was used to elevate the floor of the maxillary sinus by six mm.…”
Section: Discussionmentioning
confidence: 99%
“…Intrasinus is challenging: the electrocautery can lead to damage of Schneiderian membrane, and ligature may not be possible. Finding the intrabony component and its management can be an effective course of action ( Maridati et al, 2014 ; Yang & Lee, 2021 ).…”
Section: Discussionmentioning
confidence: 99%